2013
DOI: 10.1111/iej.12162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an improved endodontic teaching model: do preclinical exercises have an influence on the technical quality of root canal treatments?

Abstract: The application of an ERCLMD in combination with radiographs is more accurate to determine WL than radiographs alone. Students practiced the use of ERCLMDs with the new model and benefited from this experience when performing their first root canal treatments on patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…At the institution (Riyadh Colleges of Dentistry and Pharmacy), the students determine the working length using electronic apex locators and confirm it radiographically, and this may account for the relatively high percentages of acceptable length canal fillings. This result is in line with the findings of a recent study (Tchorz et al, 2014) that concluded that the early introduction of electronic apex locators during pre-clinical training improves the quality of root canals performed by undergraduate students in the clinical setting.…”
Section: Procedural Errorsupporting
confidence: 91%
“…At the institution (Riyadh Colleges of Dentistry and Pharmacy), the students determine the working length using electronic apex locators and confirm it radiographically, and this may account for the relatively high percentages of acceptable length canal fillings. This result is in line with the findings of a recent study (Tchorz et al, 2014) that concluded that the early introduction of electronic apex locators during pre-clinical training improves the quality of root canals performed by undergraduate students in the clinical setting.…”
Section: Procedural Errorsupporting
confidence: 91%
“…[23] Plans should be revised to upgrade the preclinical and clinical endodontic methods of teaching and training to fulfill the required acceptable standards. Introduction of new endodontic tools such as apex locator and nickel titanium rotary instruments will help to achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant evidence in scientific literature that the technical quality of root canal filling has a substantial effect on the outcome of root canal treatment 1,2 . Failed root canal filling is related to insufficient treatment, through technical error in the canal system of the tooth 3,4 .…”
Section: Introductionmentioning
confidence: 99%